2017
DOI: 10.1002/ptr.5872
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Curcuma longa Modulates Cell Migration and Cell–Cell Adhesion

Abstract: Cell invasion and metastasis are involved in clinical failures in cancer treatment, and both events require the acquisition of a migratory behavior by tumor cells. Curcumin is a promising natural product with anti-proliferative activity, but its effects on cell migration are still unclear. We evaluated the effects of curcumin on the proliferation, apoptosis, migration, and cell-cell adhesion of keratinocyte, oral squamous cell carcinoma (OSCC), and fibroblast cell lines, as well as in a xenograft model of OSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…It has preventive effects on tobacco smoke‐induced liver cancer (Liang et al, ). Recently, this agent has shown antimetastatic effect (de Campos et al, ; Deng, Verron, & Rohanizadeh, ). Curcumin also has cytotoxic effects on tumor cells (Khosropanah et al, ; Liu & Chen, ; Syng‐Ai, Kumari, & Khar, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has preventive effects on tobacco smoke‐induced liver cancer (Liang et al, ). Recently, this agent has shown antimetastatic effect (de Campos et al, ; Deng, Verron, & Rohanizadeh, ). Curcumin also has cytotoxic effects on tumor cells (Khosropanah et al, ; Liu & Chen, ; Syng‐Ai, Kumari, & Khar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Natural plants are considered as a huge treasure for many diseases, especially anticancer. In recent studies, more and more researchers focus on plants of Zingiberaceae, such as Kaempferia galanga, Curcuma caesia, Curcuma longa, and Alpinia officinarum, which are proven to have good anticancer effects in many cancers [34][35][36]. In this study, we focused on Amomum tsaoko, a food and traditional Chinese medicine, which is proven to have anticancer effect on liver cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…The invasion and metastasis ability of tumor cells is a common cause of tumor treatment failure (40) and curcumin can significantly inhibit these activities in tumor cells. A study of oral squamous cell carcinoma showed that curcumin reduced cell adhesion and inhibited proliferation of tumor cells with mesenchymal features (41). In addition, tumor growth factor-β1 (TGF-β1) is an important promoter of the epithelial-mesenchymal transition (EMT) in tumor cells.…”
Section: Curcumin and Tumor Proliferation Previous Studies Havementioning
confidence: 99%